The poetry of Blaise Cendrars as an expression of modern times - Araujo, Natalia Aparecida Bisio de (Lettres Françaises, 2019)
With the advent of the modern age and the poetry that emerges at the end of the nineteenth century, the connection between the literary text and reality is doubted. Denying the old concept of mimesis, critics such as Friedrich see, in modern poetry, a autotelism that made it break up with the representation of the world. However, other poets and critics, such as Mário Faustino, Adorno and Berardinelli, can not disentangle the connection of poetry with the activities of society. The work of the modern poet Blaise Cendrars is one of the examples of poetry that does not fit the Friedrich’s model because it is linked to the world, revealing the experiences that the poet had in his own experience of reality. From the theories and critics of experts of this theme, the main objective of this paper is to analyze how the poetry of Blaise Cendrars is the expression of his life and his time.